Trust enhancement in Zakat Institutions using Blockchain Technology: a qualitative approach - Zulkifri, Zulkifri; Adam Sa'ad, Auwal; Salina, Kassim; Anwar Hasan, Abdullah Othman (University of Turin, 2022)
There is an indication that zakat institutions are inefficient and lack transparency in terms of distributing and managing their funds. This leads to a lack of trust between Muzakee and zakat institutions; hence, they prefer to pay zakat to Mustahiq directly. This means that zakat institutions may be collecting far less in zakat funds than the maximum amount that is potentially available. Meanwhile, the invention of blockchain technology has disrupted the financial sector as it offers transparency in transactions, meaning intermediaries are no longer needed. The use of blockchain in zakat management is important for improving transparency in the distribution of zakat. The objective of this paper is to explore the determinant factors that influence trust in zakat institutions using blockchain technology as a mediating effect. The results of the literature review revealed that these factors are reputation, satisfaction with zakat distribution, service quality and disclosure practice. This study expects that trust in zakat institutions can be enhanced through the use of blockchain technology.